Targeting IL-17 attenuates hypoxia-induced pulmonary hypertension through downregulation of β-catenin. Issue 6 (18th February 2019) - Wang, Lei; Liu, Jie; Wang, Wang; Qi, Xianmei; Wang, Ying; Tian, Bo; Dai, Huaping; Wang, Jing; Ning, Wen; Yang, Ting; Wang, Chen
Abstract : Background: The role of interleukin 17 (IL-17) in hypoxic pulmonary hypertension (HPH) remains unclear. This study is designed to explore whether IL-17 is a potential target for HPH treatment. Methods: Clinic samples from the lung tissue and serum were obtained from qualified patients. Western blotting, immunohistochemistry and/or ELISA were used to measure the expression of relevant proteins. HPH models were established in C57BL/6 wild-type (WT) and IL-17 −/− mice and were treated with exogenous recombinant mouse IL-17 (rmIL-17) or an IL-17 neutralising antibody. Assays for cell proliferation, angiogenesis and adhesion were employed to analyse the behaviours of human pulmonary arterial endothelial cells (HPAECs). A non-contact Transwell coculture model was used to evaluate intercellular interactions. Results: Expression of IL-17 was increased in lung tissue of both patients with bronchiectasis/COPD-associated PH and HPH mouse model. Compared with WT mice, IL-17 −/− mice had attenuated HPH, whereas administration of rmIL-17 aggravated HPH. In vitro, recombinant human IL-17 (rhIL-17) promoted proliferation, angiogenesis and adhesion in HPAECs through upregulation of Wnt3a/β-catenin/CyclinD1 pathway, and siRNA-mediated knockdown of β-catenin almost completely reversed this IL-17-mediated phenomena. IL-17 promoted the proliferation but not the migration of human pulmonary arterial smooth muscle cells (HPASMCs) cocultured with HPAECs under both normoxia and hypoxia, but IL-17 had no direct effect on proliferation and migration of HPASMCs. Blockade of IL-17 with a neutralising antibody attenuated HPH in WT mice. Conclusions: IL-17 contributes to the pathogenesis of HPH through upregulation of β-catenin expression. Targeting IL-17 might provide potential benefits for alternative therapeutic strategies for HPH.